Prices versus Quantities with Morally Concerned Consumers - Klaus Schmidt; Fabian Herweg (ZBW - Leibniz Information Centre for Economics, 2021)
It is widely believed that an environmental tax (price regulation) and cap-and-trade (quantity regulation) are equally efficient in controlling pollution when there is no uncertainty. We show that this is not the case if some consumers (firms, local governments) are morally concerned about pollution and the pollution price is inefficiently low for political reasons. Emissions are lower and material welfare is higher with price regulation. Furthermore, quantity regulation gives rise to dysfunctional incentive and distribution effects. It shifts the burden of adjustment to the poor and discourages voluntary efforts to reduce pollution, while price regulation makes these efforts effective.
Keywords: D62; H23; Q52; Q58; 330; Emissions Trading; Carbon Tax; Climate Change; Prices versusQuantities; Behavioral Industrial Organization